TINGKAT PENDAPATAN ANGGOTA LMDH “LANCAR JAYA” DARI SEKTOR PERTANIAN HORTIKULTURA DI DESA NGANCAR KECAMATAN NGANCAR KABUPATEN KEDIRI - Erda Risky Saputra; Tatag Muttaqin; Nugroho Tri Waskitho (Universitas Muhammadiyah Malang, 2019)
Abstraction This research was conducted on 10 November 2018 - 31 January 2019 in Ngancar Village, Ngancar District, Kediri Regency. The study was intended to determine the level of income of LMDH